On the Problem of Modeling High Strain-Rate Behavior of Ice - Andrey Kuchmin; Andrey Abramyan (Journal of Applied and Computational Mechanics)
A model of freshwater ice behavior under impact compression is suggested. To obtain the parameters (mechanical properties of ice at high-speed loading) of the model the Kolsky method is used. The necessary parameter data are obtained at a strain rate of 1.4×103 s-1. A new procedural approach and an experimental data filtering algorithm are proposed. In addition, a phenomenological model of ice is offered, which makes it possible to obtain a relationship between the measured force and the parameters of the material. The verification of the model is performed according to the results of experiments in which forces are obtained in the study of the destruction of ice samples for high strain rates. It is shown that the analytical force model describes the experimental data well.